End of the spear - Hanon, Jim.; Ewing, Bill.; Gavigan, Bart.; Newman, Tom.; Green, Mart.; Leonardo, Louie; Allen, Chad, 1974-; Ellison, Chase, 1993-; Souza, Christina; Guzman, Jack, 1978-; Every Tribe Entertainment; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA : 20th Century Fox Home Entertainment, 2006)
Nate Saint is a pilot and Christian missionary who, with his family, lives and works in the jungles of the Amazon River Basin in South America. Nate is fascinated by tales he's heard of the Waodani, a violent and aggressive tribe living nearby, and with a group of fellow Christians takes it upon himself to teach them the importance of compassion and forgiveness. However, the leader of the Waodanis, Mincayani, does not trust the white visitors, and believes they may have had something to do with the disappearance of a young girl from his tribe years ago. A meeting between Nate and Mincayani goes terribly wrong when Nate's inability to understand the Waodani language brings himself and four of his fellow missionaries to be savagely murdered by the tribesmen. However, in the final moments of his life, Nate is able to impart a message in Mincayani that bears fruit years later when Steve Saint, Nate's son returns to continue the work his father started.
Special features: Side A: Full screen feature; "Beyond the gates of splendor" ; Side B: Widescreen feature; "Beyond the gates of splendor."
Director of photography, Robert A. Driskell Jr. ; editor, Miles Hanon ; music, Ronald Owen ; costume designer, Marian Ceo ; production designer, Clarence Major ; visual effects supervisor, David Kuklish.
Louie Leonardo, Chad Allen, Chase Ellison, Christina Souza, Jack Guzman.
MPAA rating: PG-13; for intense sequences of violence.
DVD, region 1, full screen (1.33:1) and widescreen (2.35:1) presentation; Dolby Digital 5.1 surround.
English dialogue, English, French or Spanish subtitles; closed-captioned.
Keywords: Saint, Nathaniel, -- 1923-1956 -- Drama; Missionaries -- Amazon River Region -- Drama; White people -- Relations with Indians -- Drama; Children of missionaries -- Drama; Huao Indians -- Drama; Massacres -- Ecuador -- Drama; Feature films; Video recordings for hard of hearing people